Teknik Perbanyakan Vegetatif Amorphophallus titanum dengan Perlakuan Komposisi Ekoenzim - Nadia Fitria Wulandari; Afrizal Mayub; Bhakti Karyadi (Universitas PGRI Silampari, 2024)
Amorphophallus titanum is a rare plant with high economic potential. This study aims to evaluate the effectiveness of vegetative propagation of Amorphophallus titanum through stem cuttings by providing treatment with the addition of ecoenzyme composition. Four ecoenzyme treatments with variations in vegetable composition (100%) and fruit peels (0%, 50%, 75%) were applied to stem cuttings. The materials used in the manufacture of ecoenzymes must be fresh and have not rotted or indicated mold. Ecoenzymes that have been made and fermented for 3 months, then will be analyzed for macroelements Nitrogen (N), P (phosphorus), Potassium (K). The results showed that only treatment with a 100% vegetable composition was able to increase the percentage of plant survival by 80% after 8 weeks. These results indicate that the composition of ecoenzymes has a great influence on the growth of stem cuttings of Amorphophallus titanum. The composition of ecoenzymes containing fruit peels, both singly and in mixtures, has a negative effect on plant growth. Further research is needed to identify the active compounds in ecoenzymes that affect the growth of Amorphophallus titanum.